Highly selective and reusable porphyrin-functionalized MCM-41 for efficient lead(II) removal from contaminated water: comprehensive adsorption study and real-water validation - Youssef Draoui; Smaail Radi; Mengmeng Wang; Amal El Mahdaoui; Chahrazad El Abiad; Aurelian Rotaru; Yann Garcia; M. Amparo F. Faustino; M. Graça P. M. S. Neves; Nuno M. M. Moura (Clean Technologies and Environmental Policy, 2026)

Tailoring selectivity and efficiency: pyrazolyl-1H-1,2,4-triazole MCM-41 and silica hybrid materials for efficient cadmium(II) removal from water - Youssef Draoui; Smaail Radi; Amal El Mahdaoui; Mohamed El Massaoudi; Aurelian Rotaru; Yann Garcia; Maria do Amparo F. Faustino; Maria da Graça P. M. S. Neves; Nuno M. M. Moura (Environmental Science and Pollution Research, 2025)
Two novel silica-based hybrid materials, M1 and M2 , based on silica gel and MCM-41 with a ditopic triazole-pyrazole ligand grafted onto their surfaces, respectively, were successfully synthesized and fully characterized. The adsorption capacity of these organic–inorganic hybrid materials was evaluated for copper(II), cadmium(II), and lead(II) ions. Experimental parameters including solution pH, contact time, temperature, and adsorbate concentration were systematically investigated. The obtained experimental data were analyzed using diverse adsorption isotherms and models to assess and interpret the behavior of the adsorbents. Notably, the newly synthesized materials exhibited exceptional selectivity, ultra-rapid adsorption rates within the first few minutes, and high removal efficiencies of 81.40 and 121.26 mg/g for M1 and M2 , respectively, towards Cd(II). Moreover, reusability assessments demonstrated excellent consistency, with only marginal decreases in adsorption capacities of less than 8% observed over five consecutive cycles. Interestingly, the application of M1 and M2 for the extraction of transition metals from real contaminated river water, from Nador city in Morocco, showcased their effectiveness in removing heavy metal ions even at low concentrations, with M2 achieving up to 67% cadmium removal. These findings highlight the potential of both materials as reliable systems for heavy metal removal in practical environmental remediation applications, with material M2 demonstrating superior performance over M1 . Graphical abstract

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Magnetite compensates for the lack of a pilin‐associated c ‐type cytochrome in extracellular electron exchange - Fanghua Liu; Amelia‐Elena Rotaru; Pravin M. Shrestha; Nikhil S. Malvankar; Kelly P. Nevin; Derek R. Lovley (Environmental Microbiology, 2015)
Summary Nanoscale magnetite can facilitate microbial extracellular electron transfer that plays an important role in biogeochemical cycles, bioremediation and several bioenergy strategies, but the mechanisms for the stimulation of extracellular electron transfer are poorly understood. Further investigation revealed that magnetite attached to the electrically conductive pili of G eobacter species in a manner reminiscent of the association of the multi‐heme c ‐type cytochrome OmcS with the pili of G eobacter sulfurreducens . Magnetite conferred extracellular electron capabilities on an OmcS ‐deficient strain unable to participate in interspecies electron transfer or Fe ( III ) oxide reduction. In the presence of magnetite wild‐type cells repressed expression of the OmcS gene, suggesting that cells might need to produce less OmcS when magnetite was available. The finding that magnetite can compensate for the lack of the electron transfer functions of a multi‐heme c ‐type cytochrome has implications not only for the function of modern microbes, but also for the early evolution of microbial electron transport mechanisms.